2019
DOI: 10.25035/pad.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Framing Matters: The Influence of Group-Image Threat on Reactions To Affirmative Action Policies

Abstract: Affirmative action (AA) attempts to rectify the institutional effects of prior employment discrimination toward minority groups. Although AA has played a large role in increasing workplace diversity, organizations may vary in their perspectives towards diversity itself, ranging from a sole focus on increasing diversity to appreciating the value diversity may add. Support for AA has been considered as a form of White identity management (Knowles, Lowery, Chow, & Unzueta, 2014) and is impacted by the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…This evidence is reminiscent of past findings that majority group members often believe that diversity policies do more harm than good (Dover et al, 2016;Jones et al, 2019;Nishii et al, 2018) and are inherently unfair (Gu et al, 2014;Hideg & Ferris, 2017;Leslie, 2019). However, we must note that we were unable to replicate either moderation effect in our paper.…”
Section: Majority Group Membership and Diversity Ideologysupporting
confidence: 60%
See 1 more Smart Citation
“…This evidence is reminiscent of past findings that majority group members often believe that diversity policies do more harm than good (Dover et al, 2016;Jones et al, 2019;Nishii et al, 2018) and are inherently unfair (Gu et al, 2014;Hideg & Ferris, 2017;Leslie, 2019). However, we must note that we were unable to replicate either moderation effect in our paper.…”
Section: Majority Group Membership and Diversity Ideologysupporting
confidence: 60%
“…We found that the more participants believed that diversity initiatives are generally helpful (Study 3) or the specific policy was procedurally fair (Study 4), the less likely they were to show the observed effects. This evidence is reminiscent of past findings that majority group members often believe that diversity policies do more harm than good (Dover et al, 2016;Jones et al, 2019;Nishii et al, 2018) and are inherently unfair (Gu et al, 2014;Hideg & Ferris, 2017;Leslie, 2019). However, we must note that we were unable to replicate either moderation effect in our paper.…”
Section: Brown and Jacoby-senghorsupporting
confidence: 60%
“…In the organizational context, defensive responses elicited by ingroup morality threat can increase opposition to DEI policies that draw attention to the advantaged group's moral failings (Iyer et al., 2004). When the rationale for a race‐based DEI policy was framed in terms of rectifying past discrimination (compared to highlighting the importance of diversity to the organization), for instance, White Americans reported higher levels of group‐image threat and more opposition to the DEI policy (Jones et al., 2019). Even the acknowledgement of ingroup responsibility for group‐based inequality does not necessarily lead to substantial social change, but rather is associated with limited efforts at restitution (Greenwood, 2015; Iyer & Leach, 2010).…”
Section: Threat and Opposition To Dei Policiesmentioning
confidence: 99%